2020
DOI: 10.22541/au.160430248.81465195/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A molecular method for biomonitoring of an exotic plant-pest: Leafmining for environmental DNA

Abstract: 1. Understanding how invasive species respond to novel environments is limited by a lack of sensitivity and throughput in conventional biomonitoring methods. Arthropods in particular are often difficult to monitor due to small size, rapid lifecycles, and/or visual similarities with co-occurring species. This is true for the agromyzid leafminer, Liriomyza sativae, a global pest of vegetable and nursery industries that has recently established in Australia. 2. A highly robust method based on environmental DNA (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Visual inspection methods can be limited spatially and temporally, while eDNA can persist over time and be transported easily through space. While studies exploring eDNA degradation rates on foliage are limited, agromyzid leafminer ( Liriomyza sativae Blanchard) eDNA was found 28 days after the leafmines became empty (Pirtle et al, 2021) and mammal eDNA has been reported to persist for up to 24 weeks on foliage after browsing (Nichols et al, 2012), but eDNA associated with A. tsugae wool may be protected for longer periods through shading or adsorption (Kessler et al, 2020; Kirtane et al, 2020; Valentin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Visual inspection methods can be limited spatially and temporally, while eDNA can persist over time and be transported easily through space. While studies exploring eDNA degradation rates on foliage are limited, agromyzid leafminer ( Liriomyza sativae Blanchard) eDNA was found 28 days after the leafmines became empty (Pirtle et al, 2021) and mammal eDNA has been reported to persist for up to 24 weeks on foliage after browsing (Nichols et al, 2012), but eDNA associated with A. tsugae wool may be protected for longer periods through shading or adsorption (Kessler et al, 2020; Kirtane et al, 2020; Valentin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%